Disulfiram as a novel inactivator of Giardia lamblia triosephosphate isomerase with antigiardial potential. Issue 3 (December 2017) - Castillo-Villanueva, Adriana; Rufino-González, Yadira; Méndez, Sara-Teresa; Torres-Arroyo, Angélica; Ponce-Macotela, Martha; Martínez-Gordillo, Mario Noé; Reyes-Vivas, Horacio; Oria-Hernández, Jesús
Abstract: Giardiasis, the infestation of the intestinal tract by Giardia lamblia, is one of the most prevalent parasitosis worldwide. Even though effective therapies exist for it, the problems associated with its use indicate that new therapeutic options are needed. It has been shown that disulfiram eradicates trophozoites in vitro and is effective in vivo in a murine model of giardiasis; disulfiram inactivation of carbamate kinase by chemical modification of an active site cysteine has been proposed as the drug mechanism of action. The triosephosphate isomerase from G. lamblia (GlTIM) has been proposed as a plausible target for the development of novel antigiardial pharmacotherapies, and chemical modification of its cysteine 222 (C222) by thiol-reactive compounds is evidenced to inactivate the enzyme. Since disulfiram is a cysteine modifying agent and GlTIM can be inactivated by modification of C222, in this work we tested the effect of disulfiram over the recombinant and trophozoite-endogenous GlTIM. The results show that disulfiram inactivates GlTIM by modification of its C222. The inactivation is species-specific since disulfiram does not affect the human homologue enzyme. Disulfiram inactivation induces only minor conformational changes in the enzyme, but substantially decreases its stability. Recombinant and endogenous GlTIM inactivates similarly, indicating that the recombinant protein resembles the natural enzyme. Disulfiram induces loss of trophozoites viability and inactivation of intracellular GlTIM at similar rates, suggesting that both processes may be related. It is plausible that the giardicidal effect of disulfiram involves the inactivation of more than a single enzyme, thus increasing its potential for repurposing it as an antigiardial drug. Graphical abstract: Image 1 Highlights: Disulfiram inactivates efficiently the triosephosphate isomerase of Giardia lamblia . Inactivation is species-specific; the human enzyme is insusceptible to disulfiram. Recombinant and GlTIM extracted from trophozoites inactivates similarly. Disulfiram inhibits endogenous GlTIM and trophozoite viability simultaneously. Disulfiram is a promissory option for drug repurposing against giardiasis.